Loss of nuclear TDP‐43 in amyotrophic lateral sclerosis (ALS) causes altered expression of splicing machinery and widespread dysregulation of RNA splicing in motor neurones. Issue 6 (October 2014) - Highley, J. Robin; Kirby, Janine; Jansweijer, Joeri A.; Webb, Philip S.; Hewamadduma, Channa A.; Heath, Paul R.; Higginbottom, Adrian; Raman, Rohini; Ferraiuolo, Laura; Cooper‐Knock, Johnathan; McDermott, Christopher J.; Wharton, Stephen B.; et al.
<x xml:space="preserve">Abstract</x> Aims Loss of nuclear TDP‐43 characterizes sporadic and most familial forms of amyotrophic lateral sclerosis (ALS). TDP‐43 (encoded by TARDBP) has multiple roles in RNA processing. We aimed to determine whether (1) RNA splicing dysregulation is present in lower motor neurones in ALS and in a motor neurone‐like cell model; and (2) TARDBP mutations (mtTARDBP) are associated with aberrant RNA splicing using patient‐derived fibroblasts. Methods Affymetrix exon arrays were used to study mRNA expression and splicing in lower motor neurones obtained by laser capture microdissection of autopsy tissue from individuals with sporadic ALS and TDP‐43 proteinopathy. Findings were confirmed by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) and in NSC34 motor neuronal cells following shRNA‐mediated TDP‐43 depletion. Exon arrays and immunohistochemistry were used to study mRNA splicing and TDP‐43 expression in fibroblasts from patients with mtTARDBP‐associated, sporadic and mutant SOD1‐associated ALS. Results We found altered expression of spliceosome components in motor neurones and widespread aberrations of mRNA splicing that specifically affected genes involved in ribonucleotide binding. This was confirmed in TDP‐43‐depleted NSC34 cells. Fibroblasts with mtTARDBP showed loss of nuclear TDP‐43 protein and demonstrated similar changes in splicing and gene expression, which were not present in fibroblasts from patients with sporadic or SOD1‐related ALS. Conclusion Loss of nuclear TDP‐43 is associated with RNA processing abnormalities in ALS motor neurones, patient‐derived cells with mtTARDBP, and following artificial TDP‐43 depletion, suggesting that splicing dysregulation directly contributes to disease pathogenesis. Key functional pathways affected include those central to RNA metabolism.